2017
DOI: 10.1371/journal.pone.0186340
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic uptake and radiation dosimetry of 6-[18F]fluoro-L-DOPA from PET imaging studies in infants with congenital hyperinsulinism

Abstract: The aim of this study is to assess the radiation absorbed dose of 18F-Fluoro-L-DOPA derived from the Positron Emission Tomography (PET) images of infants age ranging from 2 weeks– 32 weeks and a median age of 4.84 weeks (Mean 10.0 ± 10.3 weeks) with congenital hyperinsulinism.MethodsAfter injecting 25.6 ± 8.8 MBq (0.7 ± 0.2 mCi) of 18F-Fluoro-L-DOPA intravenously, three static PET scans were acquired at 20, 30, and 40 min post injection in 3-D mode on 10 patients (6 male, 4 female) with congenital hyperinsulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…Therefore, this technique has radically changed the surgical approach to patients with medically unresponsive HH [102,104]. A dosimetry study of 18F-DOPA derived from the PET-CT images in ten infants (median age 4.84 weeks) with HH suggested that a modest radiation dose (0.30 ± 0.04 mSv/MBq) was adequate [105]. However, there have been recent reports of its inaccuracy in precisely detecting focal lesions [106,107].…”
Section: The Role Of Real-time Continuous Glucose Monitoring (Cgm)mentioning
confidence: 99%
“…Therefore, this technique has radically changed the surgical approach to patients with medically unresponsive HH [102,104]. A dosimetry study of 18F-DOPA derived from the PET-CT images in ten infants (median age 4.84 weeks) with HH suggested that a modest radiation dose (0.30 ± 0.04 mSv/MBq) was adequate [105]. However, there have been recent reports of its inaccuracy in precisely detecting focal lesions [106,107].…”
Section: The Role Of Real-time Continuous Glucose Monitoring (Cgm)mentioning
confidence: 99%
“…This in turn induces the expression of insulin-like growth factor 2, inhibits the tumor suppressor genes H19 and cyclin-dependent kinase inhibitor 1C and leads to β-cell proliferation ( 173 ). 18 F-DOPA-PET scanning is currently the only diagnostic imaging tool to accurately localize focal lesions ( 174 ). Pancreatic islets are able to uptake L-DOPA and convert it to dopamine through DOPA decarboxylase.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated total effective dose in newborns was 2.3 6 0.3 mSv/20 MBq, which is the dose given to children with a body weight under 12.5 kg. This effective dose is significantly higher than in adults but still nearly 4-fold lower than the effective dose reported for the standard PET tracer currently used to diagnose congenital hyperinsulinism in newborns-18 F-DOPA 6-18 F-fluoro-L-3,4-dihydroxyphenylalanine-which is 0.4 6 0.04 mSv/MBq, resulting in a total dose of 8 6 0.8 mSv/20 MBq (19).…”
Section: Discussionmentioning
confidence: 78%